(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the problems of the local management bodies formation in Katerinoslavskaya region since March to October in 1917 with the use of the materials of periodicals at that time. The actuality of the working out of management problems in Ukraine is caused by the necessity of historical alternativesí reconstruction. These alternatives took place during the revolution. It analyses the significant information possibilities of periodical press, which are important for the reconstruction of the events at the time of Central Council (Rada).